INSTANT MESSAGING DALAM PERSPEKTIF EKOLOGI MEDIA DAN KOMUNIKASI - Siti Meisyaroh (SEMIOTIKA: Jurnal Komunikasi, 2014)
Technology is often described as the most important influence on society. The presence of the internet has changed the way many people communicate directly and face-to-face communication is no longer online and face to face. The emergence of a variety of media that could be a mediator of communication between individuals lead to individuals choosing to use the media because it is real time and instant without the limitations of distance and time . Instant Messaging is a popular communication media trend nowadays and most widely used by people to convey and receive messages from other individuals. The presence of a wide variety of Instant Messaging applications such as MSN, Yahoo Messenger, Google Talk, eBuddy, Blackberry Messenger (BBM), Whatapps, Kakao Talk, Chat Line until We Chat raise a variety of actions, perceptions, and experiences of communication in society . Media ecology theory perspective with the global village slogan, cold media, the electronic age and the media around the world unite together with the character and function of Instant Messaging applications to communicate and exchange messages.Keywords: Instant Messaging, Communication, Media Ecology, Internet Technology